N-Back Related ERPs Depend on Stimulus Type, Task Structure, Pre-processing, and Lab Factors - Shalchy, Mahsa Alizadeh; Pergher, Valentina; Pahor, Anja; Van Hulle, Marc M.; Seitz, Aaron R. (Frontiers in Human Neuroscience, 2020)
The N-Back, a common working memory updating task, is increasingly used in basic and applied psychological research. As such, an increasing number of EEG studies have sought to identify the electrophysiological signatures of N-Back task performance. However, Stimulus Type, Task Structure, pre-processing methods, and differences in laboratory settings, including EEG recording setup employed, greatly vary across studies, which in turn may introduce inconsistencies in the obtained results. Here we address this issue by conducting nine different variations of an N-Back task manipulating Stimulus Type and Task Structure. Furthermore, we explored the effect of the pre-processing method used and differences in laboratory settings. Results reveal significant differences in behavioral and electrophysiological signatures in response to N-Back Stimulus Type, Task Structure, pre-processing method, and laboratory settings. In conclusion, we suggest that experimental factors, analysis pipeline, and laboratory differences, which are often ignored in the literature, need to be accounted for when interpreting findings and making comparisons across studies.